THE MONITORING RESEARCHES OF HIV/AIDS ON THE BASIS OF THE SITUATION ANALYSIS - N. B. Dremova; I. V. Alekseev (IRBIS LLC, 2015)
We present the results of the analysis of the monitoring of HIV / AIDS in the regions of the Central Federal District of Russia for the period 2009-2012. With the application of complex of economic and statistical methods were identified growth trends for all nine characteristics of the epidemiological situation in the context of regions. We have identified regions with negative trends in the development of indicators, which confirms the trouble problems. The methods of multidimensional groups on thebasis of regulation and regional analysis for evaluation of the situation in regions of the Central Federal district applied for the first time. Methodical approach to assessment of the situation analysis is recommended for the monitoring of the practical health care.